Peran Pemasaran Digital, Segmentasi Pasar, dan Pengalaman Pelanggan dalam Meningkatkan Loyalitas Konsumen pada Cafe Kopi Boss Jember - Yesita Karel; Sari, Maheni Ika; Winahyu, Pawestri (Lembaga Pengembangan Kinerja Dosen, 2025)
The business competition in the culinary industry has become increasingly intense along with the development of lifestyle trends that prioritize unique and memorable consumption experiences. In such conditions, business actors are required to adopt appropriate marketing strategies in order to maintain consumer loyalty. One of the businesses facing this challenge is Cafe Kopi Boss Jember. Based on this phenomenon, this study aims to analyze the role of digital marketing, market segmentation, and customer experience in enhancing consumer loyalty at Cafe Kopi Boss Jember. This research employs a quantitative approach using a survey method through questionnaires distributed to 100 respondents who are consumers of Cafe Kopi Boss Jember, selected using purposive sampling technique. The collected data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression to examine the influence of each variable. The results of the study indicate that digital marketing, market segmentation, and customer experience have a positive effect on consumer loyalty, both simultaneously and partially. Among these variables, customer experience has the most dominant influence compared to the others. This suggests that in improving consumer loyalty, apart from utilizing digital technology and identifying the right market segments, providing a pleasant, comfortable, and memorable experience for consumers is a key factor that cannot be overlooked. The implication of this study is the importance for the management of Cafe Kopi Boss Jember to strengthen an interactive digital marketing strategy, design more targeted market segmentation, and continuously enhance the quality of customer experience through service, atmosphere, and menu innovations. These efforts are expected to sustainably increase consumer loyalty and strengthen the cafe’s competitiveness amid the fierce competition in the culinary industry.